(untitled) (Conferencea, 2024)
This article is devoted to the analysis of the role of the Supreme Council of Judges in the Republic of Uzbekistan. The article describes the main tasks, powers and implemented measures of the council in the formation of the corps of judges. This analysis is aimed at contributing to the further improvement of the judicial system.